Mobilization of plant genetic resources from South and Southeast Asia - N. P. Loskutova; T. M. Ozerskaya (Труды по прикладной ботанике, генетике и селекции, 2021)
The article is devoted to the replenishment of the VIR collection with plant genetic resources from the territories of the Philippines, Burma, Laos and Vietnam as a result of plant explorations, seed requests and germplasm exchange. In total, four collecting missions were sent to this region in the late 1970s and 1980s.Through their efforts, 2668 germplasm samples were collected and delivered to the Institute. The most numerous were the accessions of grain legumes (916), followed by vegetables (835) and groat crops (653). In addition to direct collection, the Institute was constantly engaged in requesting plant germplasm.In the prewar period, from 1925 to 1941, 396 accessions of cereal, groat, grain legume, vegetable, industrial and fruit crops were received from Burma, Vietnam, French Indochina (Laos since 1949) and the Philippines.From 1946 to 2019, 7928 accessions were added, with the largest number shipped from Vietnam (7840). Such a huge number can be explained by the activities of the Soviet breeding stations in Lai Châu Province, Northern Vietnam, and near Ho Chi Minh City, Southern Vietnam, in the 1980s and early 1990s. It should be noted that significantly fewer wild species and crop wild relatives were mobilized from these countries than from India, Indonesia and Ceylon – about 100 spp., or 10,992 accessions.Altogether, collecting teams brought from the South Asian tropical center of crop origin 18,594 germplasm samples, most of which were groat crops (4521). The prewar seed requests yielded 3520 accessions, with 1022 representing tropical woody, ornamental and medicinal plants from botanical gardens. Requests for germplasm from 1946 to the present time resulted in adding 16,687 accessions to the collection, half of which were groat crops (rice, maize and sorghum). A total of 39,161 accessions were received from the region.